(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
The purpose of this work is to study the optimized cultural conditions for the production of amylase by Aspergillus niger in solid state and submerged liquid fermentation. Four solid substrates banana peel, corn, potato and tapioca with different moisture conditions were taken for solid state fermentation (SSF). Basal medium was used for submerged liquid fermentation (SLF) with different pH (3 to 8), temperature (25, 30, 35 and 40ºC), carbon concentration (1, 2 and 3 g) and nitrogen source (0.1, 0.2 and 0.3 g). In SSF, tapioca yielded highest amylase activity and specific activity (4.43U/ml and 4.58U/mg) at 50% moisture content. In SLF, 2 g starch and 0.3 g peptone concentration showed 0.78 and 1.23 U/ml amylase activities under the optimum pH (5) and temperature (30ºC) the amylase activities reached to 0.86 U/ml and 0.76 U/ml respectively. In SSF using tapioca as substrate the enzyme yield is about five times higher than that achieved with submerged liquid culture. DOI: http://dx.doi.org/10.3329/bjsir.v47i1.7310 Bangladesh J. Sci. Ind. Res. 47(1), 99-104, 2012